PERSPECTIVE DRUG DOSAGE OF NEUTROPIC REMEDY ON THE BASIS OF EXCIPIENT FROM ROOTS OF PEGANUM HARMALA L. - H. I. Itzhanova; Zh. S. Nurmaganbetov; A. S. Mukazhanova; A. Zh. Turmukhambetov; S. M. Adekenov (Фармация и фармакология (Пятигорск))
This article represents the results of technological researches on development of new neurotropic remedy based on water-soluble excipient of harmine hydrochloride. Peroral remedy in capsules at dose of 30 mg which correspond to pharmaceutical quality indices have been developed for the first time.